Analysis and comparison of cumulative antibiograms for Charlotte Maxeke Johannesburg Academic Hospital adult intensive care and high care units, 2013 & 2017 - Law, Tina (My University, 2019)
Background. Infection is a common complication for patients in intensive care units (ICUs) and increasing antimicrobial resistance is a major concern. It is therefore crucial to monitor antimicrobial resistance patterns in order to support clinical decision making and antimicrobial stewardship strategies. Clinical microbiologists should provide annual cumulative antibiogram reports, which can be used to guide initial empirical antimicrobial therapy for the management of infections. Objectives. Analyses of the cumulative antibiograms for the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) combined adult multidisciplinary ICU and high care unit (HCU) for 2013 and 2017, comparison of the antimicrobial susceptibility testing (AST) patterns between two years; and analyses of the subset of blood culture isolates. Methods. A retrospective descriptive analysis was performed of routine bacterial and fungal culture and AST data extracted from the NHLS laboratory information system for the combined adult ICU and high care unit. Only the first diagnostic isolate of a given species per patient per year was included in the analysis. All analysis and reporting were done in accordance with the applicable Clinical and Laboratory Standards Institute guidelines. Results. Enterobacteriaceae predominated in first-isolate cultures in 2013 (60%) and 2017 (56%). There was an overall decrease in extended-spectrum beta-lactamase-producing Enterobacteriaceae from 2013 (42%) to 2017 (30%) (p=0.013), accompanied by an increase in carbapenem-resistant Enterobacteriaceae from 2013 (4%) to 2017 (11%) (p=0.24). Although the total percentage of Acinetobacter spp. decreased in 2017 (p=0.021), the proportion of extensively drug-resistant isolates doubled to 68% in 2017 (p<0.001). The percentage of MRSA decreased significantly from 49% to 14% (p<0.001), along with a significant decrease in VRE from 17% to 0% (p=0.001). Candida auris increased from 0% in 2013 to 11% in 2017 (p=0.002), and non-albicans Candida spp. predominated (80%) in blood cultures in 2017 (p=0.023). Conclusions. Appropriate selection of empiric antimicrobial therapy should be guided by the ICU-specific antibiogram. The recommended empiric antimicrobial therapy at he CMJAH ICU/HCU based on the antibiogram analysis, would include ertapenem to cover the Enterobacteriaceae. Amikacin is recommended for empiric treatment of suspected pseudomonal infections. Additional empiric antimicrobial therapy for the gram-positive organisms is not routinely advocated and empiric antifungal therapy with amphotericin B or micafungin is only appropriate in patients at high risk for invasive candidiasis.
Department of Clinical Microbiology and Infectious Diseases, School of Pathology of the University of the Witwatersrand, Johannesburg, South Africa